Implication of serum zinc level with duration and clinical type of vitiligo - Mirza, Sohail; Ali, Mohammad Eakub; Khondker, Lubna; Khan, Md. Shirajul Islam; Islam, Nadia; Rashid, Muhammad Munir (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Vitiligo is a common dermatological disorder characterized by acquired, idiopathic, progressive, hypomelanosis of the skin and hair, with total absence of melanocytes microscopically. Objective: The study was conducted to find out the relationship between serum zinc level and clinical spectrum of vitiligo. Methods: A cross sectional study conducted in the departmenl of Dermatology and Venereology and department of Biochemistry, Bangabandbu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh and the period of study was from May 2010 to October 2011. Results: The mean difference of sernm zinc level in male and female of both groups were significant (p<0.05) but the mean serum zinc level was not significantly different (p>0.05) among various clinical types ofvitiligo. ln case oflocalized vitiligo mean serum zinc level was 755.3 ± 288.6, in case of acrofacial viriligo mean serum zinc level was 821.4 ± 259.6 and in case of generalized vitiligo mean sernm zinc level was 771.6 ± 222.2. The difference of mean sernm zinc level observed between family history positive and negative group were not statistically significant (p>0.05). The difference of mean senun zinc level was also not statistically significant (p>0.05) among <1 year, 1-10 years and 11-20 years duration groups of vitiligo patients. A negative correlation (r = -0.227) was observed between duration of symptom with senun zinc level in this study. Conclusion: This study showed low level of serum zinc in vitiligo patients. Large-scale studies are needed to confirm these findings and multicenter study should be carried out to reveal the accurate pattern of zinc status in vitiligo.